Elliptically Bent X-Ray Mirrors with Active Temperature Stabilization. (26th July 2010) - Yuan, Sheng; Church, Matthew; Yashchuk, Valeriy V.; Goldberg, Kenneth A.; Celestre, Richard S.; McKinney, Wayne R.; Kirschman, Jonathan; Morrison, Gregory; Noll, Tino; Warwick, Tony; Padmore, Howard A.
Abstract : We present details of design of elliptically bent Kirkpatrick-Baez mirrors developed and successfully used at the advanced light source for submicron focusing. A distinctive feature of the mirror design is an active temperature stabilization based on a Peltier element attached directly to the mirror body. The design and materials have been carefully optimized to provide high heat conductance between the mirror body and substrate. We describe the experimental procedures used when assembling and precisely shaping the mirrors, with special attention paid to laboratory testing of the mirror-temperature stabilization. For this purpose, the temperature dependence of the surface slope profile of a specially fabricated test mirror placed inside a temperature-controlled container was measured. We demonstrate that with active mirror-temperature stabilization, a change of the surrounding temperature by more than 3 K does not noticeably affect the mirror figure. Without temperature stabilization, the rms slope error is changed by approximately 1.5 μ rad (primarily defocus) under the same conditions.